Giant Pulmonary Bullae Complicated by Hospital-Acquired Pneumonia in Chronic Obstructive Pulmonary Disease: A Multidisciplinary Approach to Successful Bullectomy - Hendra Rohmana; Darmawan Ismail (Open Access Indonesian Journal of Medical Reviews, 2025)
Giant pulmonary bullae (GPB), particularly in patients with chronic obstructive pulmonary disease (COPD), present significant management challenges due to compromised lung function. The development of hospital-acquired pneumonia (HAP) further complicates the clinical picture, increasing morbidity and mortality. This report details a case of GPB with HAP in a COPD patient. A 65-year-old male, a heavy former smoker with moderate COPD and a history of dust and wood smoke exposure, presented with progressive dyspnea and productive cough. Investigations revealed right-sided giant bullae occupying over 30% of the hemithorax, consolidation, and leukocytosis. Sputum culture grew Candida albicans, and intraoperative cultures later confirmed Streptococcus viridans HAP. Following initial medical stabilization with antibiotics, bronchodilators, and corticosteroids, he underwent an exploratory thoracotomy with bullectomy on day 14. In conclusion, the surgical intervention was successful, with no major complications. Post-operatively, the patient showed significant improvement in respiratory symptoms and lung expansion. This case highlights the efficacy of a multidisciplinary approach, combining intensive medical therapy with timely surgical bullectomy, for managing complex presentations of GPB, HAP, and COPD, leading to favorable outcomes.